CSF Surfactant Protein Changes in Preterm Infants After Intraventricular Hemorrhage - Krause, Matthias; Härtig, Wolfgang; Mahr, Cynthia Vanessa; Richter, Cindy; Schob, Julia; Puchta, Joana; Hoffmann, Karl-Titus; Nestler, Ulf; Thome, Ulrich; Knüpfer, Matthias; Gebauer, Corinna; Schob, Stefan (Frontiers in Pediatrics, 2020)
1. Introduction Surfactant proteins (SP) have been shown to be inherent proteins of the human CNS and are altered during acute and chronic disturbances of CSF circulation. Aim of the study was to examine the changes of surfactant protein concentrations in CSF of preterm babies suffering from intraventricular hemorrhage. 2. Patients and methods Consecutive CSF samples of 21 preterm infants with intraventricular hemorrhages (IVH) and posthemorrhagic hydrocephalus (PHHC) were collected at primary intervention, after 5-10 days and at time of shunt insertion approx. fifty days after hemorrhage. Samples were analyzed for surfactant proteins A,B,C and G by ELISA assays and the results were compared to 35 hydrocephalus patients (HC) without hemorrhage and 6 newborn control patients. 3. Results and discussion Premature patients with IVH showed a significant elevation of surfactant proteins SP-A, C and G compared to HC and control groups: mean values for the respective groups were SP-A 4.19 vs. 1.08 vs. 0.38 ng/ml. Mean SP-C 3.63 vs. 1.47 vs. 0.48 ng/ml. Mean SP-G 3.86 vs. 0.17 vs. 0.2 ng/ml. SP-A and G concentrations were slowly falling over time without reaching normal values. SP-C levels declined faster following neurosurgical interventions and reached levels comparable to those of hydrocephalus patients without hemorrhage. 4. Conclusion Intraventricular hemorrhages of premature infants cause posthemorrhagic CSF flow disturbance and are associated with highly significant elevations of surfactant proteins A, C and G independent of total CSF protein concentrations.